Evaluation of Nurses’ Knowledge and Attitudes toward Pain Management at Baghdad Teaching Hospitals (Indian Journal of Forensic Medicine & Toxicology, 2020)
Poorly managed or unmanaged pain is a problem that affects individuals, entire healthcare systems and societies throughout the world . Objectives: To assess nurses’ knowledge and attitudes about patient’s pain management and to find out the relationship between knowledge , attitudes and their demographical characteristic. Methodology: A descriptive cross sectional design study was carried out among 100 nurses working in male and female surgical wards, ICU, surgical ward, emergency and operating theatre of four teaching hospitals, Baghdad city. Census method was used to select the participants, in which all the nurses working in the selected wards who agreed to participate in the study were selected. Data was collected by distributing structured self-administered questionnaire which was a modified form of a standard tool, that is, Nurses’ Knowledge and Attitude Survey Regarding Pain (NKASRP) developed by Ferrel and McCaffery. Results: The majority of the study were male who accounted for (63%) of the total participants while female constituted (37%). Most of participants (49%) were ages between (18 – 27) years old, a high percentage of them were have institute graduate (40%), (50%) of the nurses were single and the remainder was married. Majority of them (37%) were employee (1-5) years in employment in nursing. Majority of them (45%) were employee (1-5) years in intensive care unit, and finally majority of nurses (77%) have training session about patient’s pain management. Conclusions: This study indicated that nurses’ have poor knowledge about pain management, as well as study indicated overall nurses’ have positive attitudes toward pain management.